Synthesis, Characterization and Ion Exchange Properties of a New Inorganic Ion Exchange Material: Zirconium(IV) Iodo-succinate - KUMAR, SANDEEP; PRASAD, S.C.; NARVI, S.S. (Asian Journal of Chemistry, 2010)
A new three-component inorganic ion exchange material zirconium(IV) iodo-succinate (ZIS) has been synthesized by adding a mixture of 0.2 M potassium iodate and 0.2 M succinic acid to 0.2 M zirconium oxychloride in different volume ratios at pH 1.0. Among several samples synthesized, ZIS-1 is selected for detailed studies owing to its highest ion exchange capacity and chemical stability. The material has been characterized on the basis of chemical composition, fourier transform infra-red and thermogravimetric studies. The ion exchange capacity of the material for Na+ ion has been found to be 3.0 meq g-1 dry exchanger. The ion exchange capacity for other ions varies and is found to be depending upon the crystal ionic radius of exchanging cations. The chemical stability of the material has been tested in acidic, neutral and basic media.